The Impact of Digital Entrepreneurship Courses and Motivation on Fostering a Green Entrepreneurial Spirit in Students' Perceptions - Kesa, Deni Danial; Wu, Mingchang; Abdillah, Fauzi; Harjadi, Dikdik; Ningsih, Arum (Qualitative and Quantitative Research Center, 2024)
Digitalization and sustainability have become two essential pillars in shaping the entrepreneurial mindset of future generations, particularly among university students. Digital entrepreneurship education is increasingly relevant in preparing technology-driven entrepreneurs. Integrating sustainability values into higher education encourages students to become innovative green entrepreneurs. Through digital entrepreneurship courses and appropriate motivational support, students can develop businesses that are not only profitable but also environmentally responsible. This study aims to analyze the impact of digital entrepreneurship courses and motivation in fostering a green entrepreneurial spirit from students’ perceptions and explore motivational factors contributing to developing a green entrepreneurial spirit. The research employed a quantitative associative method through a survey approach. Data were analyzed using partial and simultaneous hypothesis testing. The participants included 400 students from various universities in Indonesia, Taiwan, the United States of America, and the United Kingdom. The findings indicate that both partially and simultaneously, digital entrepreneurship courses and motivation significantly influence the development of a green entrepreneurial spirit in students’ perceptions. In conclusion, integrating digital entrepreneurship education with a focus on sustainability, strengthened by strong student motivation, strategically contributes to shaping a new generation of entrepreneurs who are both technologically adept and socially responsible. The contributions of this study prove that instilling sustainability values in digital entrepreneurship education is a strategic approach to fostering environmentally responsible entrepreneurship in the digital era.